CONTRADICTION RELATIONSHIP IN COMPOUND SENTENCES - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the relations of opposition in conjunctions are highlighted. Conjunctive conjunctions connect the parts of a compound sentence and express the existence of a conflicting relationship. Connected clauses are divided into connected clauses with conjunction, contrast, subtraction and negation according to their connecting means. Connected joint sentences form and of content to the relationship according to: symmetrical and asymmetric to words is divided.